Dermatofibrosarcoma Protuberans During Pregnancy: A Case Report - Elzeftawy, Shady; Elmahdy, Yousef (Brazilian Journal of Case Reports, 2026)
Dermatofibrosarcoma protuberans (DFSP) is a rare, low-grade soft tissue sarcoma characterized by local aggressiveness and high recurrence after excision. A 23-year-old primigravida at 32 weeks’ gestation presented with a progressively enlarging natal cleft mass. Biopsy confirmed DFSP (CD34 positive). Definitive surgery was performed postpartum with wide local excision and flap reconstruction, achieving clear margins. DFSP during pregnancy requires careful timing of intervention. Wide local excision with clear margins remains the treatment of choice.